2004
DOI: 10.1017/s0952836904005461
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting habitat selection by smooth‐coated otters (Lutra perspicillata) in Kerala, India

Abstract: The factors affecting habitat selection by smooth-coated otter Lutra perspicillata were studied along the Periyar Lake within the Periyar Tiger Reserve, Kerala, India, between November 2000 and April 2001. The importance of different habitat features influencing habitat selection was assessed using ordination technique. The presence of holts, spraint sites, grooming sites and footprints were considered as good indicators of the use of an area by the otters. For foraging, otters selected less rocky areas of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 20 publications
2
36
0
1
Order By: Relevance
“…Bowyer et al (1995) also reported otters' preference for shallow sites and significant correlation between otter signs and river depth and width (Ottino and Giller 2004). In Kerala's Periyar Tiger Reserve of India, otters avoided stretches of the reservoir that were deep and wide, and where the physical constraints on the animal to take deeper dives hindered their hunting ability (Anoop and Hussain 2004). In our study, streams with a depth not exceeding 5 m appeared to be preferred, thus confirming those results for otter habitat preferences.…”
Section: Ly21 Lg13supporting
confidence: 85%
See 2 more Smart Citations
“…Bowyer et al (1995) also reported otters' preference for shallow sites and significant correlation between otter signs and river depth and width (Ottino and Giller 2004). In Kerala's Periyar Tiger Reserve of India, otters avoided stretches of the reservoir that were deep and wide, and where the physical constraints on the animal to take deeper dives hindered their hunting ability (Anoop and Hussain 2004). In our study, streams with a depth not exceeding 5 m appeared to be preferred, thus confirming those results for otter habitat preferences.…”
Section: Ly21 Lg13supporting
confidence: 85%
“…This large variability, however, has its exceptions; within the range of landscapes inhabited by otters, their actual living spaces are much more specific (Anoop and Hussain 2004). Either the number of spraints or the number of sprainting sites could be used as an index of otter activity (Jenkins and Burrows 1980b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For effective conservation and restoration of this species, an understanding of its relationship with habitat parameters including historical information is required. Previously, information was presented on the factors affecting habitat selection by the smooth-coated otter in Kerala, India (Anoop & Hussain, 2004). In this paper the dietary preferences of the species in an undisturbed but anthropogenic habitat, which has been contaminated with exotic fish species such as tilapia Tilapia mossambica and European carp Cyprinus caprio communis, is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Smooth-coated otters are not restricted to deep water and often forage in small, shallow rivers (Anoop and Hussain 2004;Kruuk et al 1994) and seasonally flooded swamps during the monsoons (July-September) and early winter (October-February) in India and Nepal (Hussain and Choudhury 1997). L. perspicillata prefers habitat with rocky banks because of the greater availability of den sites (Hussain and Choudhury 1997).…”
Section: Ecologymentioning
confidence: 99%